Histórico e potencialidades da implantação do projeto de educação ambiental no modelo SAF (Sistema Agro Florestal) em uma escola pública do estado de São Paulo para o processo de ensino e aprendizagem de química - Lago, Paulo Rogério (2015)
This paper presents possible approaches concerning chemistry teaching through Environmental Education, supported by the Environmental Project, which is a themegenerator, called SAF (Agro-Forest System) implemented in a state-run school. The present research was developed by means of a collaboration of a group of students attending different high school levels. Through the Pedagogical Project, we sought to encourage students to develop research projects, relating them to scientific concepts. Our objective is to use these projects as a source for questioning the Chemistry Teaching in a contextualized approach, in which students are able to perform experiences and discuss their observations in groups. Through the act of researching, students will be exposed to chemical concepts in a different way, in a lighter manner that will enhance and transform their preconceptions, contributing to improving their understanding and interest in scientific knowledge. Aiming at defragmenting the curriculum (didactic sequence), which often impairs innovative activities, which are indispensable in teaching practices, being equally or even more important than the mastery of the studied content, this paper presents a chance to whet the curiosity of students on learning Science (Chemistry), which is widely rejected and ignored.